Electrospun ZnO nanofiber interlayers for enhanced performance of organic photovoltaic devices. (February 2020) - Mohtaram, Fatemeh; Borhani, Sedigheh; Ahmadpour, Mehrad; Fojan, Peter; Behjat, Abbas; Rubahn, Horst-Günter; Madsen, Morten
Graphical abstract: Integration of electrospun ZnO nanofibers as electron transport layers in PTB7:PC70 BM organic photovoltaic (OPV) devices is demonstrated. The devices reach a PCE of up to 7.6% and show a clear increase short-circuit current density and fill factor, from the improved extraction properties of the crystalline ZnO nanofibers. Abstract: Organic photovoltaics (OPV) has improved significantly in recent years and power conversion efficiencies are getting close to those of hybrid and inorganic thin film PV technologies. In this work, we demonstrate high performance inverted organic photovoltaic cells from electrospun nanofiber based electron transport layers, which outperform their thin-film counterpart. FTO/ZnOfilm /ZnOnanofibers /PTB7:PC70 BM/MoO3 /Ag devices were designed with different ZnO nanofiber based electron transporting layers (ETL) varying the nanofiber width and thickness, using a conventional electrospinning technique for the nanofiber ETL fabrication. We demonstrate that 35 nm thick films of electrospun ZnO nanofibers results in an improvement of the short-circuit current density (Jsc ) and fill factor (FF) in the cells, leading to power conversion efficiency of up to 7.6%. The improvement is assigned to an improved charge collection efficiency, due to realization of direct and continuous pathway for electron extraction inside the solar cell structure. The results highlight the application of one-dimensional nanofiber based charge extraction layers as a promising route for development of high performance OPV devices in the future.